Social Loafing Level of Class X Students at Senior High School 8 Semarang - Adhesty, Yulia Niken; Ismanto, Heri Saptadi (Indonesian Journal of Educational Counseling, 2024)
This research aims to determine the level of social loafing of class X students at SMA N 8 Semarang. Looking at the level of activity of class X students during the process of providing Classical Tutoring services by the guidance and counseling teacher. When the group discussion process took place there were only a few students who were actively discussing. So the researcher feels that there is a need for research regarding the level of social loafing in class X students. This research is quantitative descriptive research. The sampling technique in this research is simple random sampling. The data collection technique uses a questionnaire which contains statements stating the object to be expressed. Data analysis uses descriptive analysis techniques. The results of this research are that the level of social laziness of class X students at SMA Negeri 8 Semarang on average has a moderate level of social loafing.